Upland rice, household food security, and commercialization of upland agriculture in Vietnam - S. Pandey; Khiem, N. T; Waibel H.; Thien, T. C (Los Banos International rice research institude, 2006)
Content of the book is overview about uplands and upland rice, characteristics of upland systems and recent development trend, conceptual approach, analytical approach and descriptive analysic of farm survey data,...
Keywords: Kinh tế - chính trị